STUDENTS OF PROPER NUTRITION LESSONS ROLE AND ROLE IN LOSS - U.Sh.Maxamatov (Scholar Express Journals, 2022)
Has its own characteristics depending on the age of the student's body, the educational process and living conditions. M is given in lectures and practical classes reducing learning loads, solving and resolving various problems stage - the examination process significantly increases the state of nervousness. Exam strong excitement before and breathing during the exam, blood pressure rise and acceleration of the pulse. Especially the elementary course Primary lifestyle changes have a major impact on the body of students shows. Increasing the amount of information provided, lower education. The more time is required, the less time it takes to load facilities inability to distribute independently and organize lifestyle properly leads to an increase in mental load.
Keywords: Student meal; breakfast; lunch; tea